Bionomics in the Dragon Kingdom Ecology, Economics and Ethics in Bhutan - Tshewang, Ugyen (Fascinating Life Sciences,, 2018)
This compact and elegant work provides a readily accessible and highly readable overview of Bhutan's unique opportunities and challenges; all her prominent environmental legislation, regulatory statutes, ecological customs and practices, both in historic and contemporary terms. At the same time, Bionomics in the Dragon Kingdom places the ecological context, including a section on animal rights in Bhutan, within the nation's Buddhist spiritual and ethical setting. Historic contextualization accents the book's rich accounting of every national park and scientific reserve, as well as providing up-to-the-minute climate-change related hurdles for the country. Merging interdisciplinary sciences, engineering and humanities data in a compelling up-to-date portrait of the country, the authors have presented this dramatic compendium against the backdrop of an urgent, global ecological time-frame. It thus becomes clear that the articulated stakes for Bhutan, like her neighboring Himalayan and Indian sub-continental countries (China, India, Bangladesh and Myanmar), are immense as the Anthropocene epoch unfolds, affecting every living being across the planet. Because Bhutan's two most rewarding revenue streams derive from the sale of hydroelectric power and from tourism, the complexities of modern pressures facing a nation that prides herself on maintaining traditional customs in what has been a uniquely isolated nation are critical.